Comment on “SAT requires exhaustive search” - Allender, Eric; Williams, Ryan (Frontiers of Computer Science, 2026)
An article that was recently published in Frontiers of Computer Science claims to prove that P is not equal to NP. In fact, it claims to show that the SAT problem requires at least 2 δn time, for any constant δ ∈ (0, 1). We contend that the argument that is presented falls far short of a proof: it makes an assumption about all possible SAT algorithms that is unwarranted.